(untitled) (diségno, 2019)
“Landscapes uncontaminated by the usual aesthetic prejudices of human sight” [Moneo 1987, p. 4]: this is how José Rafael Moneo comments the works in the catalogue of the exhibition Hypnos, held in November 1986 at Harvard University and dedicated to the work of Massimo Scolari. The exhibition also included the painting Gateway for a city on the sea (Porta per città di mare), realized a few years earlier –in 1979, exactly forty years ago– and described by Scolari in the same volume in the transformation from painted landscape to physical architecture, on the occasion of the 1st Venice Architecture Biennale [Scolari 1987, pp. 54-57]. (read more)